Factors Associated with Household Waste Handling in the Rokan Iv Koto Village, Rokan Hulu Regency in 2022: Faktor-Faktor Yang Berhubungan Dengan Penanganan Sampah Rumah Tangga Di Kelurahan Rokan Iv Koto Kabupaten Rokan Hulu Tahun 2022 - Apriandi Apriandi; Novita Lusiana (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Garbage is the residue of a business or activity (human) which is solid and considered useless so that it is disposed of in the environment. Many factors influence the behavior of housewives in managing the waste they produce at home. The research method used is quantitative research with a cross sectional approach to determine the relationship between the independent variable (independent) and the dependent variable (dependent). The study was conducted in Rokan IV Koto Subdistrict, Rokan Hulu Regency, Riau Province since february until august 2022. The number of samples taken was 85 samples of housewives using stratified random sampling technique. Based on the data analysis carried out, there is no relationship between education and household waste management in Rokan I Koto District, Rokan Hulu Regency in 2022, with a P-value = 0.043 <0.05. There is no relationship between knowledge and household waste management in Rokan I Koto District, Rokan Hulu Regency in 2022, with a P-value = 0.006 <0.05. There is a relationship between attitude and household waste management in Rokan I Koto District, Rokan Hulu Regency in 2022, with a P-value = 0.047 <0.05. There is no relationship between the availability of trash bins and household waste management in Rokan I Koto District, Rokan Hulu Regency in 2022, with a P-value = 0.001 <0.05